Penerapan Aplikasi Sistem Administrasi Desa Untuk Mendukung Tata Kelolah Pemerintah Desa Di Desa Mulyoagung Kecamatan Dau - Atiek Iriany; Wigbertus Ngabu; Solimun Solimun; Achmad Efendi; Danang Ariyanto; Arditama Putra Rochmanullah (Journal of Innovation and Applied Technology, 2023)
Mulyoagung Village is a village in the Highlands which is located in Dau District, Malang Regency. The development of a tourist village requires a database and information that must be structured and systematic. One of the data and arrangement of the village administration system is related to the potential of the village or village services. Through situation analysis, this service activity tries to map the potential of the village, especially in village services. Development of village administration system applications as a tool for village officials in serving the community. The application of the village administration system application for the village of Mulyoagung is expected to be a means of providing excellent service to the community that is carried out more quickly, precisely, and accurately.  Based on the survey results, the village government is very satisfied with the village information system that has been created.